Retrofitting the BAC cloning vector pBeloBAC11 by the insertion of a mutant loxP site - Jonathon S. Coren (BMC Research Notes, 2017)
Abstract Objective Human genomic libraries constructed in bacterial artificial chromosome vectors were utilized to make physical maps of all 23-chromosome pairs and as the templates for DNA sequencing to aid in the completion of the Human Genome Project. The goal of this study was to modify the BAC vector pBeloBAC11 so that genomic inserts contained in this vector could be subjected to bidirectional transposon-mediated nested deletions from the wild-type and mutant loxP sites present. Results An oligonucleotide containing a mutant loxP 2272 site and a XhoI restriction enzyme sequence was designed and inserted at the SfiI restriction site located approximately 200 basepairs upstream of the lacZ gene in pBeloBAC11. Clones containing the desired insert were identified by XhoI restriction digests since an additional band was generated. This transposon-mediated deletion technology allows researchers to identify the boundaries of cis-acting elements and genes.